(untitled) (Research, Society and Development, 2020)
Nonalcoholic fatty liver disease (NAFLD) is characterized by fat accumulation in hepatocytes in the absence of alcohol intake and it’s the most common chronic liver disease worldwide. The pillars of NAFLD treatment are healthy lifestyle such as dietary changes, regular physical activity and gradual weight loss. This study aimed to perform an integrative review about the effects of nutraceuticals in the treatment of NAFLD. For the bibliographic survey, papers were searched in PubMed, LILACS and SciELO databases in Portuguese, English and Spanish published in the last 5 years in Portuguese, English and Spanish. The combination of the following descriptors was applied: “Non Alcoholic Fatty Liver Disease”, “Nutraceuticals” and “Diet”. The selected articles point to a relationship of omega-3, resveratrol and curcumin consumption with improvements of some markers related to NAFLD, serving as an alternative therapy in the treatment of NAFLD. Despite the effects related to the use of nutraceuticals in the treatment of NAFLD, there is a need for further research about the subject.